2021
DOI: 10.1093/infdis/jiab037
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Carriage in Burkina Faso After 13-Valent Pneumococcal Conjugate Vaccine Introduction: Results From 2 Cross-sectional Population-Based Surveys

Abstract: Background Burkina Faso, a country in Africa’s meningitis belt, introduced 13-valent pneumococcal conjugate vaccine (PCV13) in October 2013, with 3 primary doses given at 8, 12 and 16 weeks of age. To assess whether the new PCV13 program controlled pneumococcal carriage, we evaluated overall and serotype-specific colonization among children and adults during the first 3 years after introduction. Methods We conducted 2 populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A previous report comparing carriage studies conducted in Bobo-Dioulasso in 2015 (1 year post–PCV13 introduction) and 2017 (3 years post-PCV13 introduction, also included in the current study) showed reductions in VT carriage among pneumococcal carriers aged <5 years, although there were differences in the laboratory methods used for pneumococcal detection between the studies conducted in 2015 and 2017 [ 11 ]. Between 2017 and 2020, we observed no further significant reduction in VT carriage among children aged <5 years.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…A previous report comparing carriage studies conducted in Bobo-Dioulasso in 2015 (1 year post–PCV13 introduction) and 2017 (3 years post-PCV13 introduction, also included in the current study) showed reductions in VT carriage among pneumococcal carriers aged <5 years, although there were differences in the laboratory methods used for pneumococcal detection between the studies conducted in 2015 and 2017 [ 11 ]. Between 2017 and 2020, we observed no further significant reduction in VT carriage among children aged <5 years.…”
Section: Discussionmentioning
confidence: 77%
“…In March 2020, we conducted a cross-sectional, age-stratified community pneumococcal carriage study in Bobo-Dioulasso, a city located in Western Burkina Faso. We used the same recruiting methods as previous pneumococcal carriage studies conducted in Bobo-Dioulasso pre- and post-PCV13 introduction (2008, 2015, 2017) [ 11 , 16 ] and compared with data from the 2017 survey. Target sample size for each study (2017 and 2020) was 1000 persons aged ≥1 month with 200 participants each in 5 age groups: 1–11 months, 1 year, 2–4 years, 5–14 years, and ≥15 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations